The Effectiveness of Archive Management at the Makassar State Administrative Court - H, Nasaruddin; Madina, Alfira; Isgunandar, Isgunandar (Universitas Negeri Makassar, 2023)
Management is a series of activities carried out by someone who has the function and purpose of achieving a goal of the organization. Good records management supports the achievement of an organization's goals. This study aims to find out how the effectiveness of records management at the Makassar State Administrative Court. This study used a qualitative descriptive research study, while the number of informants in this study were five people with data collection techniques using the observation method, interview method, and documentation method. the data obtained from the research results were processed using data analysis techniques in this study using data reduction techniques, data presentation, conclusions and verification. The results of this study indicate that the effectiveness of Archive Management at the Makassar State Administrative Court is seen as a whole good and effective. This can be seen from the fulfillment of the indicators that are aspects of the assessment, namely storage and arrangement of archives, securing archives, maintaining archives, preventing damage to archives, and an archive depreciation system